New Insights on CMV Management in Solid Organ Transplant Patients: Prevention, Treatment, and Management of Resistant/Refractory Disease - Camille Nelson Kotton; Nassim Kamar (Infectious Diseases and Therapy, 2022)
Abstract Cytomegalovirus (CMV) infection can have both direct and indirect effects after solid-organ transplantation, with a significant impact on transplant outcomes. Prevention strategies decrease the risk of CMV disease, although CMV still occurs in up to 50% of high-risk patients. Ganciclovir (GCV) and valganciclovir (VGCV) are the main drugs currently used for preventing and treating CMV. Emerging data suggest that letermovir is as effective as VGCV with fewer hematological side effects. Refractory and resistant CMV also still occur in solid-organ-transplant patients. Maribavir has been shown to be effective and have less toxicity in the treatment of refractory and resistant CMV. In this review paper, we discuss prevention strategies, refractory and resistant CMV, and drug-related side effects and their impact, as well as optimal use of novel anti-CMV therapies.